2014
DOI: 10.1016/j.meegid.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Dual-pathogen etiology of avian trichomonosis in a declining band-tailed pigeon population

Abstract: b s t r a c tThe Pacific Coast band-tailed pigeon (Patagioenas fasciata monilis) is a migratory game bird of North America that is at risk for population decline. Epidemics of avian trichomonosis caused by upper digestive tract infection with Trichomonas spp. protozoa in these and other doves and pigeons of the United States are sporadic, but can involve tens of thousands of birds in a single event. Herein, we analyze the role of trichomonosis in band-tailed pigeon mortality and relate spatial, temporal and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 32 publications
6
51
1
2
Order By: Relevance
“…These findings show that this genotype is found among many species, including raptors, columbids and other avian species like corvids and finches over the world. Actually, this is the most frequently isolated genotype from birds with clinical signs and seems to be much more related to the presence of pathognomonic lesions than the others, as previous studies have reported (Sansano-Maestre et al, 2009;Chi et al, 2013;Girard et al, 2014b). On the other hand, the absence of oropharyngeal lesions might be explained either because some samples could have been taken at an early time in the infection and the clinical signs had not developed yet or because birds could have been immunized previously and be asymptomatic carriers of the parasite for a certain time (revised in Forrester & Foster, 2008), as occurs in other trichomonad infections (Trichomonas foetus infections in cattle, as an example).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…These findings show that this genotype is found among many species, including raptors, columbids and other avian species like corvids and finches over the world. Actually, this is the most frequently isolated genotype from birds with clinical signs and seems to be much more related to the presence of pathognomonic lesions than the others, as previous studies have reported (Sansano-Maestre et al, 2009;Chi et al, 2013;Girard et al, 2014b). On the other hand, the absence of oropharyngeal lesions might be explained either because some samples could have been taken at an early time in the infection and the clinical signs had not developed yet or because birds could have been immunized previously and be asymptomatic carriers of the parasite for a certain time (revised in Forrester & Foster, 2008), as occurs in other trichomonad infections (Trichomonas foetus infections in cattle, as an example).…”
Section: Discussionmentioning
confidence: 83%
“…isolate from a dog (AJ784785) and T. canistomae (AY244652), in comparison with other T. gallinae isolates. Girard et al (2014b) also reported T. vaginalis-like genotypes that were present only in some species and not in others, suggesting a restricted host range or the possibility of more recently evolved organisms. Genotype ITS-OBT-Tvl-5 is another newly described genotype in Spain, and to our knowledge the first detection of this genotype in the Egyptian vulture.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Genetic typing of the protozoan parasites is accomplished using PCR, identifying 15 different internal transcribed spacer (ITS) subtypes of T. gallinae isolated from a diversity of avian species, with some subtypes more commonly found in certain species (Gerhold et al., 2008, Grabensteiner et al., 2010, Sansano-Maestre et al., 2009). These subtypes have been further classified by sequencing the hydrogenosomal Fe-hydrogenase gene, of which two predominant subtypes exist, delineated A1 and A2 (Girard et al., 2014b, Lawson et al., 2011). Generally, subtype A1 is isolated from songbirds, columbids, and raptors in Europe while A2 is less commonly isolated and was recently found to be the predominant subtype isolated from Pacific Coast band-tailed pigeons ( Patagioenas fasciata monolis ) in California, USA (Girard et al., 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…These subtypes have been further classified by sequencing the hydrogenosomal Fe-hydrogenase gene, of which two predominant subtypes exist, delineated A1 and A2 (Girard et al., 2014b, Lawson et al., 2011). Generally, subtype A1 is isolated from songbirds, columbids, and raptors in Europe while A2 is less commonly isolated and was recently found to be the predominant subtype isolated from Pacific Coast band-tailed pigeons ( Patagioenas fasciata monolis ) in California, USA (Girard et al., 2014b). Genetic evaluation of the parasite gives us insight into the ecology and epidemiology of avian trichomonosis and refines our understanding of host associations, cross-species transmission, and spillover events.…”
Section: Introductionmentioning
confidence: 99%